Arginine metabolic endotypes related to asthma severity. - Weiling Xu; Suzy A A Comhair; Allison J Janocha; Abigail Lara; Lori A Mavrakis; Carole D Bennett; Satish C Kalhan; Serpil C Erzurum (PLoS ONE)
Aims Arginine metabolism via inducible nitric oxide synthase (iNOS) and arginase 2 (ARG2) is higher in asthmatics than in healthy individuals. We hypothesized that a sub-phenotype of asthma might be defined by the magnitude of arginine metabolism categorized on the basis of high and low fraction of exhaled nitric oxide (FENO). Methods To test this hypothesis, asthmatics (n = 52) were compared to healthy controls (n = 51) for levels of FENO, serum arginase activity, and airway epithelial expression of iNOS and ARG2 proteins, in relation to clinical parameters of asthma inflammation and airway reactivity. In parallel, bronchial epithelial cells were evaluated for metabolic effects of iNOS and ARG2 expression in vitro. Results Asthmatics with high FENO (≥ 35 ppb; 44% of asthmatics) had higher expression of iNOS (P = 0.04) and ARG2 (P = 0.05) in the airway, indicating FENO is a marker of the high arginine metabolic endotype. High FENO asthmatics had the lowest FEV1% (P < 0.001), FEV1/FVC (P = 0.0002) and PC20 (P < 0.001) as compared to low FENO asthmatics or healthy controls. Low FENO asthmatics had near normal iNOS and ARG2 expression (both P > 0.05), and significantly higher PC20 (P < 0.001) as compared to high FENO asthmatics. In vitro studies to evaluate metabolic effects showed that iNOS overexpression and iNOS+ARG2 co-expression in a human bronchial epithelial cell line led to greater reliance on glycolysis with higher rate of pyruvate going to lactate. Conclusions The high FENO phenotype represents a large portion of the asthma population, and is typified by greater arginine metabolism and more severe and reactive asthma.